Highlights of the 25th Conference of the European Society for Microcirculation: Integrating vascular biology and medicine: Basic and clinical science August 26-29, 2008, Budapest, Hungary - Koller, A; Bagi, Z (2009)
Although not complete, the above described cross section of avenues of today research in microcirculation, blood rheology and vascular biology - we believe - will lead us not only to a better understanding how circulation of organs are designed and regulated and affected by various conditions, but also will help us to design new modalities to temper pathophysiological alterations in microcirculation. © 2009 S. Karger AG, Basel.